2003
DOI: 10.1053/jhep.2003.50022
|View full text |Cite
|
Sign up to set email alerts
|

Expression profiling in multistage hepatocarcinogenesis: Identification of HSP70 as a molecular marker of early hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) associated with chronic liver disease evolves from precancerous lesions and early HCC to a progressed form. Nodule-in-nodule-type HCC (progressed HCC within early HCC) represents the transition from early to progressed HCC and, therefore, is useful in molecular genetic analysis of HCC progression during multistage carcinogenesis. We compared expression profiles among 7 early components and 7 progressed components of nodule-in-nodule-type HCCs and their corresponding noncancerous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
206
2
3

Year Published

2003
2003
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 282 publications
(221 citation statements)
references
References 35 publications
10
206
2
3
Order By: Relevance
“…HSP70 is, in particular, a potent antiapoptotic survival factor. Chuma et al 47 reported HSP70 as the most abundantly up-regulated gene among a set of 12,600 genes in early HCC. Furthermore, it was significantly overexpressed in progressed HCC as compared with early HCC, and in the latter as compared with precancerous lesions.…”
Section: Emerging Tumor Markersmentioning
confidence: 99%
“…HSP70 is, in particular, a potent antiapoptotic survival factor. Chuma et al 47 reported HSP70 as the most abundantly up-regulated gene among a set of 12,600 genes in early HCC. Furthermore, it was significantly overexpressed in progressed HCC as compared with early HCC, and in the latter as compared with precancerous lesions.…”
Section: Emerging Tumor Markersmentioning
confidence: 99%
“…Because such thickened trabecular structure cannot mix with noncancerous tissue, advanced HCCs show distinct margin even in a liver with an early stage of chronic liver disease. Various tumor markers, that is, HSP70, GPC3, and GS, also show incrementally more intense expression from early to advanced HCCs [25][26][27][28][29][30][31]. Vascularities of the tumors also change according to tumor development.…”
Section: Developmental Process Of Hccs From Early Stage To Advanced Smentioning
confidence: 99%
“…In addition to the morphological criteria, some attempts have been made recently to utilize immunohistochemical markers for the diagnosis of well-differentiated HCCs [25][26][27][28][29][30][31]. Heat shock protein 70 (HSP70) [25,26], glypican 3 (GPC3) [25,[27][28][29], and glutamine synthetase (GS) [25,30,31] have been used independently or in combination.…”
Section: Total Process Of Biopsy Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to their responsiveness to diverse forms of stress, the stress proteins have undergone widespread application in biomonitoring and environmental toxicology [5,[34][35][36][37][38][39][40][41]. As members of the Hsp70 are often the prominent proteins to be expressed following environmental insults, these stress proteins are, therefore, very useful indicators of cellular aggression, and have been used to monitor the impact of environmental factors on various animal species [42][43][44][45] as well as in in vitro models [28,37,41,46,47]. Hsp70 is the target molecule or molecule under investigation because it simultaneously takes part in defense, repair, or detoxification machinery of the cell and becomes a direct and specific indicator of cellular stress [30,[48][49][50][51].…”
Section: Hsp70 In Environmental Monitoringmentioning
confidence: 99%